An Empirical Study on Water Resources Development & Management and its Repercussions on Indian Agriculture - Charu Singh; Prabha Rani; Kishore Kumar (International Journal of Mathematics And its Applications, 2023)
India is endowed with a rich and vast diversity of natural resources. Water is one of the most essential natural resources for sustaining life. Its development and management play a vital role in agriculture production. Integrated water management is vital for poverty reduction, environmental sustenance, and sustainable economic development. With rapid growing population and improving living standards the pressure on our Water Resources is increasing and per capita availability of Water Resources is reducing day by day. Water availability per person is dependent on population of the country and for India, per capita water availability in the country is reducing due to increase in population. The average annual per capita water availability in the years 2001 and 2011 was assessed as 1816 cubic meters and 1545 cubic meters respectively which has further reduced to 1486 cubic meters cubic meters in the years 2021. The paper presents availability and demands of water resources in India as well as describes the various issues and strategies for developing a holistic approach for sustainable development and management of the water resources and its implication on Agricultural Production of the country.